INFLUENCE OF DISEASES ON LIVING PARENTS OF THE CHILD WITH ASTMA - PILOT STUDY - Valancová, Alena; Gurková, Elena (Profese Online, 2009)
The goal was to map the impact of asthma bronchiale on the quality of life for families with children with the disease. Through a questionnaire to measure the quality of life of families child with asthma, Pediatric Asthma Caregiver's Quality of Life Questionnare, the authors looked subjective perception of the impact of disease on the lives of parents of children with asthma and problem areas in life that most concerns parents. The sample consisted of 21 parents whose children have Recondition stay in the High Tatras. Based on analyzing the data found that the disease interferes with the most emotional experience of parents, their fear of the future child. Parents reported that the illness struck at least within their areas of employment, running the household and they suffer the least time to pay for childcare in the context of the disease. Identifying the extent the impact of disease on the lives of parents can be the basis for planning adequate education of children and their parents, which would affect the emotional management, change attitudes and actions in relation to the disease.
Keywords: bronchiale asthma; influence of disease; quality of life